A LOOK AT THE HISTORY OF CLUB ESTABLISHMENTS AND CULTURAL AND EDUCATIONAL PROCESS IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides important historical information on the activities of the first clubs in the territory of Uzbekistan. It was noted that clubs are an important tool in the cultural and educational life of our people, the stages of development and a tool for political and ideological influence on the population. Scientific research and studies have been conducted on the cultural and political services of clubs around the world in Uzbekistan, the involvement and active participation of interested people in the club. Recommendations are given for the practical study of club science, which is the original root of the field of culture and art, only if it is scientifically permissible.